The two poles of ancient biography and hagiography (Circe de clásicos y modernos, 2020)
Greek biography can be associated to two main poles: on one of them the syntagmatic axis, with succession, predominates; on the other, the paradigmatic axis, without succession. The first pole is related to historiography and has a method closer to ἱστορία; its best-known ideal type is the energetic or Peripatetic hagiography (Plutarch). The second pole is related to demonstrative rhetoric, its method is closer to antiquarianism and it appears in the analytic or Alexandrian biography (Suetonius). This contribution will suggest that in the usual hagiography this opposition is visible in a separated treatment of “life” and “deeds”, often summarized in the titles by Βίος καὶ πολιτεíα: the succession of facts, situated in time and space, as opposed to a timeless character, which reveals itself rather than becomes. To this aim, I will discuss the basic features of biography; describe F. Leo’s theory about classical biography; examine M. Bakhtin’s biographical chronotope, and his indebtedness with authors such as Leo or G. Misch; analyse some crucial features of hagiographical discourse and of its peculiar chronotope; and offer a brief conclusion.
Keywords: biography; hagiography; Bakhtin; Leo; genres